2015
DOI: 10.1007/s00380-015-0775-9
|View full text |Cite
|
Sign up to set email alerts
|

Clinical benefit of tolvaptan in patients with acute decompensated heart failure and chronic kidney disease

Abstract: Tolvaptan, a vasopressin type 2 receptor antagonist, has an aquaretic effect without affecting renal function. The effects of long-term tolvaptan administration in heart failure patients with renal dysfunction have not been clarified. Here, we assessed the clinical benefit of tolvaptan during a 6-month follow-up in acute decompensated heart failure (ADHF) patients with severe chronic kidney disease (CKD; estimated glomerular filtration rate (eGFR) <45 mL/min/1.73 m(2)). We compared 33 patients with ADHF and se… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

2
21
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 36 publications
(23 citation statements)
references
References 30 publications
2
21
0
Order By: Relevance
“…There was no report that tolvaptan was associated with longer survival time in patients with heart failure [19][20]. On the other hand, some reports showed that tolvaptan responders were associated with longer survival time in cirrhotic patients [8,[21][22][23].…”
Section: Discussionmentioning
confidence: 91%
“…There was no report that tolvaptan was associated with longer survival time in patients with heart failure [19][20]. On the other hand, some reports showed that tolvaptan responders were associated with longer survival time in cirrhotic patients [8,[21][22][23].…”
Section: Discussionmentioning
confidence: 91%
“…Uemura, et al retrospectively evaluated the change in creatinine and rehospitalization up to 6 months after discharge, and concluded TLV prevented increase of creatinine and rehospitalization. 22) The present study showed continuous TLV administration (average administration period: 347 ± 212 days) could prevent medium-term WRF and decrease its associated long-term adverse outcomes. Therefore, together with findings from previous studies, TLV might be an effective therapy to improve medium-term clinical outcomes as well as long-term outcomes.…”
Section: Discussionmentioning
confidence: 95%
“…10 Tolvaptan alleviates volume status and clinical symptoms in patients with congestive heart failure, [11][12][13][14][15] although the clinical outcomes in heart failure patients (mostly without diabetes) with renal insufficiency were inconsistent. [16][17][18] Patients with heart failure who were nonresponsive to tolvaptan were shown to have higher serum creatinine levels. 19 Additionally, decreased renal function attenuates tolvaptan-induced free water clearance.…”
mentioning
confidence: 99%